Comparing the Effectiveness of Sensory Integration Exercises on Stereotyped Behaviors With and Without Robot in Boys With Autism Spectrum Disorder - Vahideh Emad; Mahnaz Estaki; Roya Koochak Entezar (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Autism spectrum disorder in children manifests as qualitative degradation in communication and developing stereotyped patterns in behavior and interests. Some researchers believe that the reason for creating stereotyped patterns in children's behaviors is some sensory impairment in response to sensory stimuli. Children with autism spectrum can use endorsed and predictable systems such as computers. Robots may be used as friends or assistant therapists to teach various social and cognitive skills. The present study aimed to compare the effectiveness of sensory integration exercises on stereotyped behaviors with and without robots in boys with autism spectrum disorder.Methods This research method was quasi-experimental with a pretest-posttest and follow-up design with a control group. The statistical population comprised all boys aged 7-9 years studying in Tehran boys' autism schools (the academic year 2018-2019). Of whom, 45 children with autism were selected by convenience sampling and randomly assigned to two experimental groups (sensory integration exercises with and without robots) and one control group. Data were collected using the stereotyped behaviors section of the second edition of the Gilliam Autism Diagnosis Test (1994) in the pretest, posttest, and a 2-month follow-up. Both experimental groups used the 15-session sensory integration method, but one group also worked with the robot for 15 sessions. The control group received no intervention. The obtained data were analyzed using repeated measures analysis of variance and the Bonferroni post hoc test with SPSS 22 software at a significance level of 0.05.Results The results showed that the changes in stereotyped behavioral disorders were different in the three groups. The study of significant effects showed that in the experimental situation, the mean scores of the sensory integration exercises using the robot decreased more than those without the robot and the control group (P<0.05). Conclusion Findings show that combining sensory integration therapy and robot therapy improves the stereotypical behaviors of children with the autism spectrum more than sensory integration therapy alone.